2013
DOI: 10.3390/ijms140816240
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Thyroid Hormone Signaling in the Prevention of Digestive System Cancers

Abstract: Thyroid hormones play a critical role in the growth and development of the alimentary tract in vertebrates. Their effects are mediated by nuclear receptors as well as the cell surface receptor integrin αVβ3. Systemic thyroid hormone levels are controlled via activation and deactivation by iodothyronine deiodinases in the liver and other tissues. Given that thyroid hormone signaling has been characterized as a major effector of digestive system growth and homeostasis, numerous investigations have examined its r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 122 publications
0
37
0
2
Order By: Relevance
“…However the final consequence of this influence depends on the sampled population and the tumor type. Excellent reviews have been published in the last years on this respect [61][62][63][64][65]. Some examples of these studies are shown in Table 1 for hyperthyroid conditions and Table 2 for hypothyroidism.…”
Section: Thyroid Status and Tumor Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…However the final consequence of this influence depends on the sampled population and the tumor type. Excellent reviews have been published in the last years on this respect [61][62][63][64][65]. Some examples of these studies are shown in Table 1 for hyperthyroid conditions and Table 2 for hypothyroidism.…”
Section: Thyroid Status and Tumor Progressionmentioning
confidence: 99%
“…Respect to digestive system cancers, TH signaling has been associated to the prevention of disease [63], and accordingly it was demonstrated that long-term thyroid hormone replacement treatment in hypothyroid patients was related to a significantly reduced relative risk of colorectal cancer [74,75]. Also, increased risk of hepatocellular carcinoma in hypothyroid subjects was also demonstrated by 2 case-control studies [76,77] However contradictory results were found in the relation between hypothyroidism and the development of other cancer types.…”
Section: Thyroid Status and Tumor Progressionmentioning
confidence: 99%
“…Components of thyroid hormone signaling are implicated in the development and progression, as well as in the prevention of various cancers including hepatocellular carcinoma (HCC) [ 1 3 ]. HCC usually develops in patients with liver cirrhosis [ 4 , 5 ] and represents the second most common cause of cancer-related mortality in men globally [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the epithelial domain our analysis shows the enrichment of Thyroid hormone signaling pathway that has been associated with a tumor suppressive role in CRC development. 55,56 In contrast, the bacterial invasion pathway, enriched in epithelial-stromal boundary region, has been implicated in the oncogenic role of the colonic microbiome in CRC development. 57,58 Our analysis also reveals enrichment of certain other pathways, such as the hypoxiainducible factor 1 (HIF-1), human epidermal growth factor receptor 2 (HER2) and T-cell receptor signaling pathways in the epithelial domain.…”
Section: Spatial Domain Network Reveal Domain-specific Network Biolomentioning
confidence: 99%